GOOD PRACTICES AND PRODUCTIVITY: An analysis to verify the perceptions caused in MSEs assisted by the ALI Program - Local Innovation Agents in Cycles from 2021 to 2024 (REMUNOM, 2025)
There are few studies that attempt to explain an increase in productivity levels through the adoption of Good Practices. The objective of this work is to identify the perception of managers of MSEs assisted by the ALI Program in relation to increased productivity through the adoption of good management practices implemented after their participation in the ALI Program - Sebrae Local Innovation Agents. The research, with a qualitative and quantitative approach, using a survey in 151 companies and with questioning adapting the dimensions and variables of the SERVQUAL model. The results obtained revealed the positive effect of using Good Practices in gaining Productivity. As contributions, the study leaves important conclusions regarding this practice, which can constitute a low-cost strategy that only brings benefits to the segment.